Making sense of bodily experiences: Interpreting signs and symptoms - Morison T; Gibson A (Massey University, 2025)
This chapter is about how people make sense of the changes experienced in their bodies as an indication of illness. How do we know when a physical sensation is serious or just a fleeting discomfort? Deciding whether to seek medical care or ignore a symptom is a daily reality, but the process of interpreting bodily signals is far more complex than it might seem. By the end of this chapter, you will be able to understand symptom interpretation as more than a straightforward process. Instead, you will see it as a complex, socially negotiated act with significant implications for individual health, healthcare practices, and broader public health outcomes.